APLIKASI KONSEP FITOTEKNOLOGI DALAM PEMBELAJARAN BIOLOGI PADA SEKOLAH HIJAU - Widowati, Hening (Bioedukasi Jurnal Pendidikan Biologi, 2010)
Phytotechnology plays as integral strategy for planning and environment sanitation process. Phytoprocess on phytotechnology makes possible the realization of healthy environment mission, because plant have ability to recycle material, as natural so as environment resources conservation technology, which essential in continuously development. Green school have commitment with systematic develop programs for internalyzing environment value to school activity. Applying phytotechnology concept is systematic strategy for realization of biology learning at Green School Education Program.              Kata kunci: fitoteknologi, sekolah hijau